MOLECULAR AND CELLULAR MECHANISMS MEDIATED BY DENDRITIC CELLS INVOLVED IN THE INDUCTION OF TOLERANCE - S. V. Sennikov (SPb RAACI, 2017)
Autoimmune diseases  and  complications  after  transplantation  operations are  major   public health  problem, as they often  lead to deterioration in the quality  of life, reduce  work capacity  and  disability in the  population. To date, the  induction of antigen-specific tolerance is the  promising method of therapy. During this process dendritic cells play important role.  In  this review current data  of tolerogenic dendritic cells characterization, of factors inducing tolerogenic properties in dendritic cells, development of central  and peripheral tolerance by dendritic cells, role of tolerogenic dendritic cells in the formation of regulatory B cells, molecular and cellular mechanisms that are involved in the formation of an immunological tolerance depending on tolerogenic dendritic cells were analyzed. Tolerogenic dendritic cells play a key role in maintaining of immune homeostasis by inducing immunological tolerance mechanisms which  are associated with the  generation of regulatory T cells, induction of anergy or apoptosis of T cells. Formation of tolerogenic properties in dendritic cells is occurred by various factors that regulate the maturation and differentiation of dendritic cells and induce anti-inflammatory agents synthesis of them. Because of their ability to induce natural and peripheral regulatory T cells, dendritic cells contribute to the development of the central  and peripheral tolerance in the organism. Analysis of the results  of experimental work demonstrates that  in addition to induction of regulatory T cells tolerogenic dendritic cells participate in generating of regulatory B cells that  play a role in the  formation of tolerance and  have the  ability  to affect  the  population of regulatory T cells. However, the  mechanisms that lead to the formation of B cell population by tolerogenic dendritic cells have not been completely established yet. Review of published data showed that the molecular and cellular mechanisms of immunological tolerance induction by tolerogenic dendritic cells and other regulatory cell subpopulations interacting with each other are similar to a large extent.  Currently, the role of tolerogenic dendritic cells in maintaining of immune tolerance is determined generally, however, some aspects  require  further  investigation. Subsequent experimental studies will lead to a better understanding of the signaling mechanisms and the realization of immunological functions of tolerogenic dendritic cells, which provide additional information for application approaches development of tolerogenic dendritic cells for the control of autoimmune diseases and transplant complications.